Raising Community Early Awareness of Acute and Chronic Kidney Failure - Parulian Dormaida Gultom; Rifka Banjarnahor; Rudianto Aritonang; Cindi Oktaviani Panjaitan; Ester H.N Simanjuntak; Desi Simanjuntak (CV. AFDIFAL MAJU BERKAH, 2025)
Kidneys are vital organs that perform several crucial functions to maintain overall health like filtering waste, regulating blood pressure, and producing red blood cells. Despite their importance, kidneys problems are often overlooked in daily health routines until they become serious. This makes it crucial to adopt habits that support kidney health. Raising early awareness of acute and chronic kidney failure is essential for early detection and prevention, since these conditions often go unnoticed, especially in primary care. Increased awareness about kidney failure should extend beyond specific high-risk groups and healthcare professionals to encompass the general public. This article focused on a health education initiative to improve community awareness about kidney disease and its management. The aim of this activity is to empower individuals with the knowledge and understanding to adopt healthy lifestyles and make informed decisions about their health, thereby enhancing their overall quality of life. The community service activities program was carried out in Pardomuan Nauli Village, Laguboti District, Toba Regency in June 2024. There is a growing understanding of individuals to take proactive steps how to prevent kidney failure, both acute and chronic conditions, for their own health, at the practical level in their daily life